Telling digital stories as feminist research and practice: A 2-day workshop with migrant women in London. Issue 1 (April 2018) - Vacchelli, Elena; Peyrefitte, Magali
In this article, we look at Digital Storytelling (DS) as a specifically feminist epistemology within qualitative social research methods. Digital Storytelling is a process allowing research participants to tell their stories in their own words through a guided creative workshop that includes the use of digital technology, participatory approaches, and co-production of personal stories. The article draws on a 2-day Digital Storytelling workshop with migrant women which was set up to understand the life stories and work trajectories of volunteers working in the women's community and voluntary sector in London. By outlining this innovative approach, the article highlights its potential and makes a case for Digital Storytelling as a feminist approach to research while taking into account epistemological, practical, and ethical considerations.